Eficiencia energética en la empresa de lácteos Leito ubicada en el cantón Salcedo, 2013. - Pérez Mayorga, Javier Isaías (2018)
The present study was carried out in the Industry - Dairy LEITO, located in Salcedo canton, where it has been identified that energy consumption and the lack of audit programs and energy efficiency increase production costs. The objective was to evaluate the energy consumption and propose a better use of the company´s energy resources by analyzing the performance of thermal and electrical equipment and the adoption of technical-organizational measures that allow achieving savings of the energy inputs to reduce costs of production by this issue. The study was based on the methods and calculations specified in the IRAM standard, ISO50001, for the electrical analysis national regulation was used 1160, regulation CONELEC - 004/011. The results of the study show low yields in the systems of refrigeration and steam generation. These parameters can be improved with the control and adjustment of refrigeration equipment and steam generation, the change of technology in refrigeration system compressors and the commissioning of control systems that the company has.